ANALISIS PENGARUH E-SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION YANG BERDAMPAK PADA CUSTOMER LOYALTY PT BAYU BUANA TRAVEL TBK - Doddy Mulyadi Saputra; Sumpena Sumpena; Yuma Akbar (STIKOM CKI, 2018)
ABSTRACTThe purpose of this study is to determine the effect of e-service quality on customer satisfaction and its impact on customer loyalty of PT Bayu Buana Travel, Tbk. With non-probability technique (census), questionnaires were collected and used in data processing using Structural Equation Modeling with WarpPLS program and Importance Performance Analysis methods. Based on this research, it was found that e-service quality has an influence on customer satisfaction, customer satisfaction has an influence on customer loyalty, e- service quality has an influence on customer loyalty, and e-service quality and customer satisfaction has an influence on customer loyalty. The e-service quality attributes, such as the website providing accurate information, the website having a good reputation, all online payment be confirmed, the website easy to use, and the products/services on the website delivered according to the time, need to be improved and enhanced.Keywords: e-service quality, customer satisfaction, customer loyalty, structural equation model, important performance analysis